2017
DOI: 10.1002/bies.201700036
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and insulin resistance: New targets encourage new thinking

Abstract: Summary Galectin-3 and LTB4 are pro-inflammatory molecules recently shown to directly cause insulin resistance in mouse and human cells. They are highly expressed in the obese state, and can be targeted both genetically and pharmacologically to improve insulin sensitivity in vivo. This expands on previous research showing that targeting inflammatory cytokines can be insulin sensitizing in animal models. However, translating these potential therapies into the human setting remains challenging. Here we review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Phosphorylation of IRS-1 at Ser307, a potential mechanism underlying insulin resistance, attenuates insulin signaling pathways (19). It has been shown that targeting antiinflammatory cytokines might restore insulin sensitivity (27,28). Furthermore, diabetic drugs with anti-inflammatory properties protect against cardiovascular complications in patients with type 2 diabetes (29).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of IRS-1 at Ser307, a potential mechanism underlying insulin resistance, attenuates insulin signaling pathways (19). It has been shown that targeting antiinflammatory cytokines might restore insulin sensitivity (27,28). Furthermore, diabetic drugs with anti-inflammatory properties protect against cardiovascular complications in patients with type 2 diabetes (29).…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant decrease in M1 macrophage gene expression by BBR, which was significantly increased by LTB4 [ 39 ]. The possible mechanism of BBR could be related to its effect on the LTB4–BLT1 axis, known as a target for treating metabolic diseases [ 40 ]. As a consequence of this interaction, BBR mediated the down-regulation of p-NF-κB expression in macrophages caused by LTB4 [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to classical pro-inflammatory cytokines, Gal-3 is also considered a key factor leading to insulin resistance. Gal-3 expression is up-regulated in CD11c + macrophages isolated from the adipose tissue of insulin resistant obese mice, but not after these mice had been changed to a normal chow diet and become insulin sensitive [11]. The cytokines secreted by the inflamed immune cells may contribute to the improvement of glycolipid metabolism after the depletion of CD11c + cells by the piperine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokine galectin-3 (Gal-3) plays a vital disease-exacerbating role in autoimmune/inflammatory diseases including obesity-associated diabetes [11]. Gal-3, an approximate 31-kDa protein with a specific carbohydrate recognition domain and a conserved N-terminal domain, functions as an inflammatory mediator [12], which is mainly secreted by M 1 -like macrophages in visceral adipose tissues and can directly enhance macrophage chemotaxis.…”
Section: Introductionmentioning
confidence: 99%